INDISCIPLINE IN THE EARLY GRADES OF FUNDAMENTAL EDUCATION AT ESCOLA MUNICIPAL RAIMUNDO ROBERTO DE CARVALHO - Melo dos Anjos, Valdemir (Revista Gênero e Interdisciplinaridade, 2024)
The present study have to address the topic of indiscipline, which is very pertinent and much discussed in the educational field, because the indiscipline issues in the school caused by the students have left many education professionals worried. Since the indiscipline runs through all segments of basic education, thinking about some possible solutions, through the theme, the following question came up: What are the challenges of the teacher of the initial series of Basic Education I of the Raimundo Roberto de Carvalho School to promote the fight to indiscipline? This article has as general objective: to know the challenges of the teacher of the initial series of Elementary School I to promote the fight against indiscipline. The article proposed and analyzed the causes and effects of indiscipline in the initial series, being used evaluation techniques, for it allows a greater observation of the subject in question, having as stages of the research: bibliographical survey and theoretical-methodological deepening. The subject proposed by the researcher has relevance for teaching praxis since it can promote an analysis of strategies for coping with indiscipline in the school environment. As for the lack of limits, several ideas arise that support this fact as: family disruption, conflicts and social issues, as well as the disorders of global development.